ACUTE AND CHRONIC GASTRITIS AND GASTRODUODENITIS IN CHILDREN - Kenjayeva Fotima Uskumbayevna; Kenjayev Sardor Bakhtiyar ogli (Web of Journals Publishing, 2026)
Nowadays, among children, chronic gastritis and gastroduodenitis, as well as peptic ulcer disease of the stomach and duodenum, constitute a major part of gastrointestinal disorders. Therefore, having sufficient knowledge about these diseases, taking timely preventive measures, and starting treatment early make it possible to control these conditions completely and avoid potential complications. This article describes the causes, clinical presentation, treatment, and prevention of chronic gastritis and gastroduodenitis, and peptic ulcer disease of the stomach and duodenum.
Keywords: Gastritis, secretion, infiltration, dyspeptic syndrome, meteorism, atrophy, gastroenteritis, gastroscopy, hyperthermia, metaplasia, intoxication, regeneration, fibro esophagogastroduodenoscopy (FEGDS), gastroduodenitis.